The great kapok tree : a tale of the Amazon rain forest - Cherry, Lynne (Harcourt Brace Jovanovich, 1990)
The many different animals that live in a great kapok tree in the Brazilian rainforest try to convince a man with an ax of the importance of not cutting down their home.